2001
DOI: 10.5172/conu.11.1.55
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of medication errors between two storage sites

Abstract: This prospective single-blinded study aimed to compare the types of medication errors and medication error rates of two medication delivery systems. The setting was a 30 bed surgical ward that was divided into two identical areas. In one area medications were stored and issued in a ward bay workstation immediately outside the patients' rooms. The alternate area used a medication trolley at the patients' bedside. Three hundred and forty opportunities for errors were observed using five nurse educators. Twenty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…With respect to medication safety, previous studies in Australia and Northern Ireland have found a statistically significant difference in error rates favouring bedside medication lockers compared to standard centralised medication trolley systems . Medications were less likely to be omitted and were more likely to be given on time when they were issued and administered at the patients' bedside .…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…With respect to medication safety, previous studies in Australia and Northern Ireland have found a statistically significant difference in error rates favouring bedside medication lockers compared to standard centralised medication trolley systems . Medications were less likely to be omitted and were more likely to be given on time when they were issued and administered at the patients' bedside .…”
Section: Introductionmentioning
confidence: 95%
“…Bedside medication lockers are a widely used medication management storage solution chosen by many hospitals, regardless of whether they are for new ward areas or for refurbishment of old areas. This shift in how medications are stored is generally aimed at improving medication administration efficiency by nursing staff, increasing patient contact and improving medication safety …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations